Higher Education Institution Marketing: Factors Influencing Students' Decision To Choose Politeknik Negeri Medan (POLMED) - Mayako, Puja Afwanda; Wulandari, Poppy (Universitas Persada Indonesia YAI, 2025)
This study aims to analyze the factors influencing students' decisions to choose Politeknik Negeri Medan (POLMED) as their higher education institution. Higher education in Indonesia has experienced rapid development; however, competition among educational institutions has become increasingly intense. With a large number of both public and private higher education institutions, the challenge faced by each institution is how to compete and attract prospective students. POLMED, as one of the state universities in North Sumatra, must be able to implement effective marketing strategies to attract students. The research method used is a qualitative approach, with in-depth interviews conducted with students at POLMED. The findings indicate that the marketing strategies applied by POLMED, such as collaborations with schools, promotion through social media, and the organization of campus events, have proven to be effective in enhancing POLMED's visibility among prospective students. However, there is room for improvement, particularly in digital marketing. Students suggest that POLMED should improve its digital content to be more engaging and relevant to the interests of the younger generation, such as videos showcasing campus activities, alumni testimonials, and more detailed information about the advantages of vocational education.